The effect of interactive learning videos on informatics learning outcomes: A quasi-experimental study with junior high school students - Dochi Ramadhani; Dewi Sulistiyarini; Febrianto Sabirin; Yolanda; Nunik Esti Utami (Universitas PGRI Pontianak, 2026)
This study was conducted to determine the effectiveness of interactive learning videos on junior high school students’ Informatics learning outcomes in computational thinking material in terms of gender. The research employed an experimental method with a nonequivalent control group design. The results showed that prior to the treatment, the initial abilities of both groups were relatively similar, with the mean pretest scores of the experimental group at 45.17 and the control group at 45.71. After the treatment, both groups showed an increase in learning outcomes; however, the experimental group achieved a higher mean score of 83.61 compared to 73.05 in the control group. The ANCOVA results indicated a significant difference between the two groups after controlling for prior knowledge (p < 0.001), while gender did not have a significant effect on learning outcomes (p > 0.05), and no interaction was found between instructional model and gender. Based on these findings, it can be concluded that interactive learning videos are effective in improving students’ Informatics learning outcomes in computational thinking and can be applied consistently regardless of students’ gender.